Reconstruction of the Kafaah Concept in Marriage - Suwarjin Suwarjin (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2022)
construction of kafaah contains discriminatory and problematic nuances. This can be seen from the criteria for kafaah, which are all physical-material, except for religion and piety. Humans are polarized into primordial partitions: beautiful-ugly, rich-poor, aristocratic-ordinary people, and free-slave. This polarization gives birth to discriminatory attitudes in society. In fact, Islam came to eliminate discriminatory social barriers. Through the maqâshid al-syâri`ah approach, this research seeks to reconstruct the concept of kafaah in several aspects, namely: reorienting the purpose of applying kafaah, repositioning kafaah rights, reviewing kafaah criteria and classifying kafaah. Maqâshid al-syâri`ah is presented here not as a doctrine to understand a particular context of Islamic law, but as a method to reconstruct the existing concept of kafaah. The goal is to produce a new concept of kafaah that is more substantive and humanist. From the results of the study, several conclusions were found. First, Kafaah legality is ijtihad because there are no valid texts found. Second, The construction of kafaah is influenced by the patrilineal system of Arab society. Third, Reconstruction of the concept of kafaah is carried out in two ways: (1) to include other criteria other than the seven criteria set by classical fiqh. (2) to compare the kafaah criteria between prospective husbands and prospective wives holistically. This things needs to be done to fulfill the current sense of justice and benef of the Muslim family. Kafaah dalam pernikahan bertujuan mewujudkan keluarga yang utuh dan harmonis. Namun, konstruksi lama tentang kafaah mengandung nuansa diskriminatif dan problematik. Ini dapat dilihat dari kriteria kafaah yang seluruhnya bersifat fisik-material, kecuali agama dan kesalihan. Manusia dipolarisasi kedalam sekat-sekat primordial: cantik-jelek, kaya-miskin, ningrat-rakyat biasa, merdeka-budak dan seterusnya. Polarisasi inilah yang melahirkan sikap diskriminatif dalam masyarakat. Padahal, Islam datang untuk menghilangkan sekat-sekat sosial yang diskriminatif. Melalui pendekatan maqâshid al-syâri`ah penelitian ini berusaha merekonstruksi konsep kafaah pada beberapa aspek, yaitu: reorientasi tujuan pemberlakuan kafaah, reposisi hak kafaah, meninjau ulang kriteria kafaah dan pengklasifikasian kafaah. Maqâshid al-syâri`ah di sini dihadirkan bukan sebagai doktrin untuk memahami konteks tertentu hukum Islam, melainkan sebagai metode untuk merekonstruksi konsep kafaah yang telah ada. Tujuannya, untuk menghasilkan konsep baru mengenai kafaah yang lebih substantif dan humanis. Dari hasil penelitian didapati beberapa kesimpulan. Pertama; legalitas kafaah bersifat ijtihadi karena tidak ditemukan nash yang sahih. Kedua; Konstruksi kafaah dipengaruhi oleh sistem patrilineal masyarakat Arab. Ketiga; Rekonstruksi konsep kafaah dilakukan dengan dua cara, yaitu: (1) menyertakan kriteria lain di luar tujuh kriteria yang ditetapkan fikih klasik. (2) membandingkan kriteria kafaah antara calon suami dan calon istri secara holistik. Hal ini perlu dilakukan untuk memenuhi rasa keadilan dan kemaslahatan kekinian keluarga Muslim.